Karakterisasi Lima Isolat Cendawan Endofit Tanaman Padi Sebagai Agen Antagonis Pyricularia Oryzae - Ika Nur Fatimah; Tunjung Pamekas; Hartal Hartal (University of Bengkulu, 2020)
Endophytic fungi are microorganisms that live in plant tissues or plant organs, such as seeds, leaves, flowers, stems and roots which are able to induce plant resistance to diseases. Local isolate of endophytic fungi are expected more effective to control diseases. Blast disease, that caused by Pyricularia oryzae, is a limited factor on rice paddy production. This study aim was to characterize dan select endophytic fungi isolates isolated from rice paddy as antagonistic agents to control P. oryzae. The research methods were survey rice paddy in the field, isolation and characterization of endophytic fungi isolates, isolation and characterization of P. oryzae, and testing the mechanism of antagonism of endophytic fungi isolates and P. oryzae in vitro by dual culture test. The results showed that there were five endophytic fungi isolated from rice paddy, that were Aspergillus candidus, Gliocladium sp, Trichoderma harzianum, Penicillium sp, and Nigrospora sp. The eight isolates of endophytic fungi were isolated from various sites having different micro environment. Endophytic fungi isolated from rice paddy at the district of Central Bengkulu demonstrated highest inhibition percentage, which was 85.60% with competition for space, nutrition, and oxygen, antibiosis, and hyperparasitism.